Penerapan latihan plyometric frog jump pada penjaga gawang di klub sepakbola Cikal Fc Kabupaten Musirawas - Belli, Deki; Friansah, Drajat; Remora, Hengky (Ilmu Olahraga, 2022)
This study aims to determine the effect of plyometric frog jump training on the increase of goalkeeper long pass kicks in Cikal FC club, Musirawas Regency. The method used was pseudo-experimentation. The sample consisted of 4 goalkeepers with the sampling technique, namely total sampling. Collecting data in the study using a test, namely the long pass kick. Data analysis techniques with the steps: normality test and t test. The results of the data analysis show that the value of tcount> ttable is 7,835> 2,353, the average result of pre test and post test has increased by 9,12. This shows that the application of the plyometrics frog jump training method provides a significant increase in the results of the goalkeeper's long pass kicks at the Cikal FC Club, Musirawas Regency.